Asymmetric Brook Rearrangement. Issue 1 (4th December 2018) - Lee, Nicholas; Tan, Choon‐Hong; Leow, Dasheng
Abstract: Although the Brook rearrangement has been discovered over fifty years ago, there remains significant opportunities for chemists to make new discoveries relating to this reaction. Majority of the examples in the literature report Brook rearrangements using racemic starting materials. In this Focus Review, we highlight asymmetric variants of Brook rearrangements, focusing on enantioselective and enantiospecific examples. Abstract : Left or right : This Focus Review highlights the recent advancements in asymmetric Brook rearrangement, which is a rapidly evolving field. Several contemporary approaches are presented.